2014
DOI: 10.1007/s10867-014-9346-z
|View full text |Cite
|
Sign up to set email alerts
|

Sharp intense line in the bioluminescence emission of the firefly

Abstract: Numerous investigations have been carried out on the spectral distribution of the light of different species of fireflies. Here we record the emission spectrum of the Indian species of the firefly Luciola praeusta Kiesenwetter 1874 (Coleoptera : Lampyridae : Luciolinae) on a color film. Green and red color-sectors, with an intense yellow one in between, appear in this spectrum. Intensity profile of this spectrum reveals a hitherto undetected strong narrow yellow line, which lies within the full-width-at-half m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Figure 3 shows the spectrum recorded on a colour film in the glass spectrograph with its intensity profile. Similar to the one for L. praeusta 7,8 , this spectrum also reveals three colour sectors: two broad sectors of green and red, and one narrow sector of yellow. It is also apparent that the yellow photons deviate less than the other two colours.…”
supporting
confidence: 60%
See 2 more Smart Citations
“…Figure 3 shows the spectrum recorded on a colour film in the glass spectrograph with its intensity profile. Similar to the one for L. praeusta 7,8 , this spectrum also reveals three colour sectors: two broad sectors of green and red, and one narrow sector of yellow. It is also apparent that the yellow photons deviate less than the other two colours.…”
supporting
confidence: 60%
“…As the calibration of the spectrometer was nearly perfect, and determination of wavelengths in the spectrum recorded in the spectrograph was done with the help of standard lines of iron, the obvious speculation is that a very sharp line is likely to exist at 579 nm. A similar paradox in the case of L. praeusta has recently resulted in the observation of a strong narrow yellow line in its emission spectrum 8 . In the present case, the reason for non-observation of the 579 nm line could be the nonresponse of the spectrometer precisely at this wavelength.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…20 Very recently, a sharp intense yellow line at 591 nm was detected in the emission spectrum of this species of the firefly, the intensity of which fluctuates widely even at a fixed temperature. 26 Hence one cannot be conclusive about the colour change of bioluminescence with temperature in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that the time-resolved spectrum in the microsecond scale of this species exhibited resemblance with the output of a multimode laser 3 . A striking finding in recent times has been the appearance of a narrow strong line at 591 nm in the emission spectrum of this species; it has been hypothesized that the emission of this line is akin to that of a random laser 6 . Very recently, the steady-state spectrum recorded for another Indian species, Asymmetricata circumdata in a high-resolution spectrometer has shown the peak wavelength at 570 nm, while the same on a colour film in a glass spectrograph revealed the peak at 579 nm between green and red bands, prompting speculation that a sharp line might exist in the emission spectrum of this species just as in the case of L. praeusta 7 .…”
mentioning
confidence: 99%